ISLAMIC ETHICS IN BUSINESS COMPETITION - Jaya Miharja (Muamalat: Jurnal Kajian Hukum Ekonomi Syariah, 2019)
The issuance of Law No.5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition, at least shows how important there is a regulation that specifically regulates the behavior of entrepreneurs in the business competition which is getting tougher from time to time. This aims to protect small and medium businesses so that they can compete competitively and there is no centralization of economic power in just one or a group of people, as happened in the past.